Epigenetically Mediated Pathogenic Effects of Phenanthrene on Regulatory T Cells - Jing Liu; Luhua Zhang; Lisa C. Winterroth; Marco Garcia; Shannon Weiman; Jillian W. Wong; John B. Sunwoo; Kari C. Nadeau (Journal of Toxicology)
Phenanthrene (Phe), a polycyclic aromatic hydrocarbon (PAH), is a major constituent of urban air pollution. There have been conflicting results regarding the role of other AhR ligands 2,3,7,8- tetrachlorodibenzo-p-dioxin (TCDD) and 6-formylindolo [3,2-b]carbazole (FICZ) in modifying regulatory T cell populations (Treg) or T helper (Th)17 differentiation, and the effects of Phe have been understudied. We hypothesized that different chemical entities of PAH induce Treg to become either Th2 or Th17 effector T cells through epigenetic modification of FOXP3. To determine specific effects on T cell populations by phenanthrene, primary human Treg were treated with Phe, TCDD, or FICZ and assessed for function, gene expression, and phenotype. Methylation of CpG sites within the FOXP3 locus reduced FOXP3 expression, leading to impaired Treg function and conversion of Treg into a CD4+CD25lo Th2 phenotype in Phe-treated cells. Conversely, TCDD treatment led to epigenetic modification of IL-17A and conversion of Treg to Th17 T cells. These findings present a mechanism by which exposure to AhR-ligands mediates human T cell responses and begins to elucidate the relationship between environmental exposures, immune modulation, and initiation of human disease.